The Historical Development of the Hungarian Plea Bargain - Kelemenné Csontos, Laura (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
The new Criminal Procedure Code entered into force on 1 July 2018. Based on the experience of the last four years, the settlement has not been popular, but confession at the preparatory session has become favoured. Hungarian academic literature considers the settlement to be the institution closest to the American plea bargain. In addition to the two new legal institutions, the Criminal Procedure Code contains several simplifier options. Both the previous and the current Criminal Procedure Code provide successful simplifier tools (e.g., penalty order), however, neither the settlement nor its predecessor — the waiver of trial — could break through. In my PhD study I am looking for the answer to why the Hungarian plea bargain cannot break through, for which purpose I examine the antecedents of the settlement from a historical point of view. A fundamental shortcoming can be observed: similarly, to German criminal procedure law, the principle of consensus as a legitimizing principle is missing from Hungarian criminal procedure. It would be worthwhile to examine the results that the introduction of the consensus principle would lead to. In addition, it would be important to examine the different simplifier institutions in relation to each other, i.e., to which groups of cases and how they are applied. It is possible that the aim of speeding up procedures may be reached more conveniently by the authorities by other simplifier solutions.